Innovation and human failure in small-scale audiovisual archives – what do we need to learn from each other? - Jahnechen, Gisa; Musib, Ahmad Faudzi; Homsombat, Thongbang; Meddegoda, Chinthaka Prageeth; Xiao, Mei (International Association of Sound and Audiovisual Archives (IASA), 2018)
Based on several previous studies presented at IASA annual conferences (2001, 2005, 2009, 2013, 2014, 2015, 2017) this paper intends to summarize long-term outcomes with a focus on the innovation needed in the digital era and the possible human failure in small-scale archives such as those the authors work with in Asia. In this paper, all authors[1] follow their specific question with the purpose of contributing to an analytic view on how technology collides with or creates a sense of community. Our emphasis is on sharing positive experiences and encouraging others by honestly discussing possible failures due to various conditions. Embedding these possible failures into a wider context is part of a mutual learning process. At the same time, each author will address a different clientele of stakeholders such as educational institutions, governmental decision makers, academia, occasional users, and the AV archivists themselves. [1] The authors know each other and have networked through the activities of the panel organizer in all these institutions over the last two decades.